Єврейське шкільництво на теренах Київського навчального округу (80–90-ті рр. ХІХ ст.) - Іваненко, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
Статтю присвячено діяльності початкових державних і приватних
єврейських навчальних закладів на теренах Київського навчального округу
впродовж 80–90-х рр. ХІХ ст. На основі аналізу матеріалів періодичної
преси, а також документів (зокрема і вперше запроваджених до наукового обігу) фондів «Канцелярія київського, подільського й волинського
генерал-губернатора» (ф. 442) та «Канцелярія попечителя Київського
навчального округу» (ф. 707) Центрального державного історичного
архіву України м. Києва, висвітлюється культурно-освітнє життя єврейської громади. Аналіз освітньої діяльності євреїв відкриває перспективи більш глибокого осмислення динаміки їхнього соціально-демографічного розвитку, місця та ролі в культурному житті українських
губерній, впливу державних структур на регламентацію внутрішнього
життя єврейської спільноти. Конкретно-історичний матеріал щодо
культурно-освітньої діяльності єврейської громади наприкінці ХІХ ст.
складає основу для з’ясування співвідношення спрямованості євреїв на
збереження власних традицій, з одного боку, та здатності адаптації до
іншокультурного соціуму, з іншого. The article deals with activities of primary state and private Jewish
educational institutions in the Kiev educational district during the eightiesnineties
of the 19th century. The author analyzes cultural and educational life
of the Jewish community on the basis of press materials and documents of the
funds “the Chancellery of the Kyiv, Podillya and Volyn General Governorate”
(f. 442) and “the Chancellery of the trustee of the Kyiv educational district”
(f. 707) of the Central State Historical Archives of Ukraine (Kyiv). The analysis
of Jews’ educational activity offers the prospect of better understanding the
dynamics of their socio-demographic development, the place and role in the
cultural life of Ukrainian provinces, the influence of state structures on the
regulation of internal life of the Jewish community. The material concerning
the history of cultural and educational activities of the Jewish community in the
late nineteenth century forms the basis for an understanding of the balance
between orientation of Jews to the preservation of their own traditions, on the
one hand, and ability to adapt to a different society, on the other. Russification
policies in education, aimed at the assimilation of the younger generation,
played a key role in the imperial strategy of destruction of the Jewish
community’s traditional lifestyle and cultural identity.
The problems of Jewish population’s adaptation to the Russian Empire’s
multilayered socio-cultural landscape, the interaction with the state authorities
of the post-reform period (1880–1890s), the incorporation of Jewish communities
into an administrative imperial system, the transformation of the
traditional lifestyle, the everyday culture of Jews, the development of interethnic
relations are key in the understanding the specifics of Dnipro Ukraine’s
historical development as a unique space of the interaction of various cultural
phenomena.